Digital Transformation in Cooperative Enterprises: A Strategy for Nigeria’s Socioeconomic Development (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined digital transformation in cooperative enterprises as a strategy for enhancing Nigeria’s socioeconomic development. Specifically, the study sought to examine the extent of digital transformation adoption among cooperative enterprises, identify the digital technologies utilized in improving operational efficiency and service delivery, and assess the effect of digital transformation on the financial performance and productivity of cooperative enterprises in Nigeria. Cooperative enterprises remain critical instruments for grassroots development, financial inclusion, employment generation, and poverty reduction; however, their effectiveness has been constrained by limited technological adoption, inefficient management systems, and poor data management practices. The study adopted a descriptive survey research design using a mixed-method approach. Data were collected from 360 cooperative societies selected across the six geopolitical zones of Nigeria. The study was anchored on the Technology Acceptance Model (TAM). Descriptive statistics, including frequencies, percentages, means, and standard deviations, were used to analyze the data, while regression analysis was employed to test the hypotheses. The findings revealed that digital transformation significantly enhances cooperative governance, financial management, communication, and record-keeping systems. Approximately 72% of respondents reported increased operational efficiency following the adoption of digital technologies. The regression results indicated a strong positive relationship between digital transformation and cooperative performance (R = 0.79, p < 0.05), with digital financial management, communication technologies, and electronic record-keeping contributing significantly to improved productivity and organizational effectiveness. However, major challenges affecting digital transformation include inadequate ICT infrastructure, limited technical skills, high implementation costs, and insufficient funding. The study concluded that digital transformation is a viable and strategic tool for improving the sustainability, efficiency, and competitiveness of cooperative enterprises, thereby contributing significantly to Nigeria’s socioeconomic development. The study recommends the establishment of government-private sector partnerships to support cooperative digitalization, provision of digital literacy and capacity-building programs, improvement of ICT infrastructure, and formulation of supportive policies that facilitate the integration of digital technologies into cooperative operations nationwide.
Keywords: Digital Transformation; Cooperative Enterprises; Technology Adoption; Cooperative Governance; Operational Efficiency; Socioeconomic Development; Nigeria